2017
DOI: 10.4028/www.scientific.net/kem.751.643
|View full text |Cite
|
Sign up to set email alerts
|

PMMA Demonstrated Higher Elastic Modulus and Nanohardness Compared with Polyamide Denture Base Materials

Abstract: The elastic modulus and nanohardness of denture bases may be different based on the type of material. The purpose of this study was to compare the elastic modulus and nanohardness of polyamide and polymethyl methacrylate (PMMA) denture base materials. Three polyamide denture base materials (Valplast, Lucitone FRS, and Thermoplastic Comfort System (TCS)) and one Polymethyl methacrylate (PMMA,Triplex Hot) denture base material (n=10) were evaluated to compare their elastic modulus and nanohardness values using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The result of previous study showed the PMMA modulus of elasticity was 5,88 ± 0,2 GPa and the hardness was 0,27 ± 0,01 GPa [12]. Modulus of elasticity in TCS ® was 1,9 ± 0,1 GPa and the hardness was 0,09 GPa [16,17]. Modulus of elasticity in Biotone ® was 1340 ± 50 MPa [18].…”
Section: Discussionmentioning
confidence: 99%
“…The result of previous study showed the PMMA modulus of elasticity was 5,88 ± 0,2 GPa and the hardness was 0,27 ± 0,01 GPa [12]. Modulus of elasticity in TCS ® was 1,9 ± 0,1 GPa and the hardness was 0,09 GPa [16,17]. Modulus of elasticity in Biotone ® was 1340 ± 50 MPa [18].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in polymer science have resulted in innovative polymers with higher impact strength and fatigue resistance, high-impact polymers and fiber-reinforced polymers, for example [5]. Inorganic fillers such as metallic oxides, fluorinated glass fillers, hydroxyapatite whiskers, zirconia, and carbon/graphite, aramid, ultra-high modulus polyethylene, nylon, and jute are used to modify the polymer [2,6]. In the dental literature, there are reviews of investigations on polymeric alterations.…”
Section: Introductionmentioning
confidence: 99%